PENINGKATAN KINERJA SISWA DALAM PEMBELAJARAN IPA DENGAN MODEL PEMBELAJARAN INQUIRY DI MI TARBIYATUS SHIBYAN KEMBIRITAN GENTENG BANYUWANGI - Kurniyatul Faizah (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2017)
This research is a classroom action research (CAR). The action was done in two cycles. The subjects of research were 34 pupils of year-5 students of MI Tarbiyatus Shibyan Kembiritan Genteng Banyuwangi. The data were collected through observation, documentation, interviews and test which were performed during the learning process, while the test was administered in the end of every cycle. The data included (1) qualitative data of the students’ performance which were classified in five categories; 5 = excellent, 4 = good, 3 = fair, 2 = poor, 1 = very poor, and (2) quantitative data of the students’ achievement test with the score ranging from 0 to 100. The evaluation of the students’ performance was held by means of giving score towards a set of the students’ performance in the learning process. The data were analyzed by determining the average score of every student’s performance, and therefore determining each category into excellent, good, fair, poor or very poor.The result of this research revealed that There was improvement in the students’ performance as indicated by: (1) the increase in the average score of the students’ performance which 2.86 or in the fair category increases to 3.57 or in the good category; and (2) the increase in the average score of the test which 79.26 increases to 85.00.There was 97.1% of students who obtained good accumulative grade above the minimum mastery level standard required that is 65. Therefore, it can be concluded that there was an improvement of students’ performance through the implementation of learning inquiry model.